Zeolite Characterization and Catalysis A Tutorial - Chester, Arthur W.; Derouane, E.G. (Springer Netherlands, 2010)
Zeolites have been an important material in catalysis and other applications (adsorbents, detergents) for the last 50 years. While new types of porous materials (ordered mesopores, metal organic frameworks) are now attracting more R&D attention, zeolites are still the most important crystalline industrial catalysts. Zeolite Characterization and Catalysis: A Tutorial makes available a series of tutorials on zeolite characterization and catalysis. Topics covered include X-ray powder diffraction, infra-red and Raman spectroscopy, Electron microscopy, determination of acid/base properties, the important reactions of C1 building blocks over zeolites as well as zeolite catalysis in chemicals . An important chapter covers computational methods in zeolite science. Zeolite Characterization and Catalysis: A Tutorial is intended for graduate students, post-docs and experienced scientists entering the fields of synthesis, characterization and catalytic applications of porous materials.